Secular inflation - Lage, Friedrich-Karl. (Dordrecht, Holland : D. Reidel Publishing Company, 1961)
The object of this treatise is, therefore to establish when and where long term money depreciation occurred, and how this problem has been dealt with by national economist.
Bibliography/Notes: p. 68-84.
osa; 15/08/18
Loans
Keywords: Inflation (Finance)